Angle-specific ross coefficient for PV modules operating in tropics - Chieng, Eric You Liang (2022)
It is crucial to predict the operating temperature of a PV module accurately as the performance of a PV module decreases when its operating temperature increases. The Ross coefficient model is one of the well-known module temperature models used to predict the operating temperature of a PV module. The Ross coefficient model is associated with the in-plane solar irradiance, and ambient and module temperature. However, this model has a low accuracy when estimating the PV module temperature because the Ross coefficient is usually determined from the gradient of a regression line from a long period of meteorological data, which scatters widely in a plot. In this project, an improved version of the Ross coefficient is introduced. This improved model is named as the angle-specific Ross coefficient model, where the sectionalised of the Ross coefficient according to the sun incident angle on the plane of collection and time is considered. The result shows that the angle-specific Ross coefficient changed drastically over the sun incident angle and deviated significantly from the Ross coefficient. Besides, it was also noticed that the intercept point of the regression line of the scatter plot at the y-axis (y-intercept) should not be fixed at the origin, as what the regression line of the conventional Ross coefficient model does. In fact, this y-intercept point varies over the sun incident angle and should be included as an additional parameter in the angle-specific Ross coefficient model. The variation of the angle-specific Ross coefficient and the corresponding yintercept was evaluated and discussed. Other models such as the time-specific Ross coefficient model, Sandia model, and Faiman model were also analysed and discussed in this project. Lastly, all the models mentioned above were applied to a case study to predict the PV module temperature for evaluating their accuracy. After the evaluation, it was found that the angle-specific Ross coefficient has the highest accuracy.